2019
DOI: 10.1146/annurev-astro-081817-051832
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Galaxy Evolution Through Emission Lines

Abstract: We review the use of emission-lines for understanding galaxy evolution, focusing on excitation source, metallicity, ionization parameter, ISM pressure and electron density. We show that the UV, optical and infrared contain complementary diagnostics that can probe the conditions within different nebular ionization zones. In anticipation of upcoming telescope facilities, we provide new self-consistent emission-line diagnostic calibrations for complete spectral coverage from the UV to the infrared. These diagnost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
480
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 436 publications
(512 citation statements)
references
References 432 publications
(469 reference statements)
18
480
0
Order By: Relevance
“…Our ξ ion measurements are lower compared to model predictions and such differences could be driven by differences in the stellar population/ISM properties (e.g., Kewley et al 2019), calibration uncertainties, and/or the choice of the dust attenuation curve. In Nanayakkara et al (2016) we showed that the relative calibration between ZFIRE spectra and ZFOURGE photometry agrees within 10%.…”
Section: The Observed Distribution Of ξ Ionmentioning
confidence: 55%
“…Our ξ ion measurements are lower compared to model predictions and such differences could be driven by differences in the stellar population/ISM properties (e.g., Kewley et al 2019), calibration uncertainties, and/or the choice of the dust attenuation curve. In Nanayakkara et al (2016) we showed that the relative calibration between ZFIRE spectra and ZFOURGE photometry agrees within 10%.…”
Section: The Observed Distribution Of ξ Ionmentioning
confidence: 55%
“…As discussed in Kewley et al (2019) and in Section 4.3, small-scale (< 100 pc) observations are the missing piece to disentangle the contribution of contaminating factors to galaxy-wide quantities and relations between these. A prominent example of this is the effect of the diffuse ionized gas on measurements of e.g.…”
Section: The Diffuse Ionized Gasmentioning
confidence: 99%
“…The grey shaded region shows a 0.3 dex spread from the one-to-one relationship. In some cases, the optical metallicity errors may be underestimated, and ±0.3 dex represents the typical systematic errors inherent in optical strong line methods (Kewley et al 2019b).…”
Section: [Si Iii] λ18831893mentioning
confidence: 99%